A Dark- Adapted Eye - Vine B. Barbara (London, Penguin Books, 1994)
England in the fifties was not kind to women who erred, so they had to use every means necessary to keep the truth hidden behind closed doors, even murder. No onlooker would guess that prim Vera Hillyard and her beautiful, adored younger sister, Eden, were locked in a dark and bitter combat over one of those secrets.